A new species of Chlamydia isolated from Siamese crocodiles (Crocodylus siamensis). - Somjit Chaiwattanarungruengpaisan (Public Library of Science (PLoS), 2021)
Chlamydia is a known pathogen in both saltwater and freshwater crocodiles. However, the exact species/strain has not been clearly identified. In this study, we successfully cultivated Siamese crocodile Chlamydia in McCoy cells at a temperature of 30°C. Electron microscopy; phylogeny based on nine conserved taxonomically informative markers, on ompA, or on seven housekeeping genes; and whole-genome sequencing and analysis of the isolate confirmed the identity of the isolate as a new member of the genus Chlamydia, a new species that we name Chlamydia crocodili.